Quantitative oxidation of Thiourea and Some of Its Derivatives with Ammonium Hexanitratocerate(IV) Reagent In Nitric Acid Medium at Micro State - Chauhan, R.P.S.; Syraiya, Afshan (Asian Journal of Chemistry, 2010)
An accurate method has been described for the detennination of thiourea, phenylthiourea, allylthiourea and o-ditolylthiourea at the mg level with the use of ammonium hexanitratocerate(IV) as the oxidant. The sample is reacted with an excess of Ce(IV) solution at room temperature (25°C) for about 30 min, the unreacted Ce(IV) reagent is then determined by titrating against Fe(II), using ferroin indicator. The precision and accuracy are within ±1 %.